Challenges With Strengthening Exercises for Individuals With Knee Osteoarthritis and Comorbid Obesity: A Qualitative Study With Patients and Physical Therapists. Issue 1 (20th December 2021) - Lawford, Belinda J.; Bennell, Kim L.; Allison, Kim; Schwartz, Sarah; Hinman, Rana S.
Abstract : Objective: To explore challenges associated with implementing a home‐based strengthening exercise program for individuals with knee osteoarthritis and comorbid obesity. Methods: This is a qualitative study embedded within a randomized controlled trial comparing 2 home‐based strengthening programs (weight‐bearing functional exercise versus non–weight‐bearing quadriceps strengthening exercise) for individuals with knee osteoarthritis and comorbid obesity. Patients in both exercise programs attended 5 consultations with a physical therapist and undertook a home‐based exercise program for 12 weeks. After trial completion, semistructured individual telephone interviews were conducted with 22 patients and all 7 physical therapists who delivered trial interventions. Interviews were recorded, transcribed verbatim, and thematically analyzed using an inductive approach. Results: Three themes arose: 1) psychological challenges (false assumptions about exercise; fear of pain; disliking exercise; mental effort of the weight‐bearing functional program; underestimating capability); 2) physical challenges (complexity of the weight‐bearing functional program; cuff weights and straight leg raise being problematic in non–weight‐bearing quadriceps program; other health conditions); and 3) overcoming challenges (incentives to exercise; accountability; education and reassurance; tailoring the exercise program). Conclusion: Patients and physical therapists experienced numerous psychological and physical challenges to exercise, including a fear of pain, having false assumptions about exercise, difficulties with exercise performance, application of cuff weights, and adverse impacts of other health conditions.